Konstytucyjne gwarancje wolności osobistej. Rozważania de lege ferenda - Daszkiewicz, Wiesław (Wydział Prawa i Administracji UAM, 1989)
Personal freedom is one of the interests which were very early counted among the rights of an individual declared and protected by constitutions. The Constitution of the Polish People's Republic of 1952 generally grants to citizens personal inviolability and stresses that the deprivation of liberty may take place only in instances determined by law. In Polish law legal titles of the deprivation of liberty are highly diversified. They comprise repressive measures, e.g. the deprivation of liberty for criminal offences and transgressions, and to some extent, e.g. in military law, for disciplinary delicts, preventive measures in criminal proceedings, arrest and preliminary detention, executive measures in civil and criminal proceedings, forced hospitalization, e.g. of people with contagious diseases, or of people who commited offences but who require medical treatment in isolation due to the threat they constitute to others, measures applied towards addicts. internment in extraordinary situations, measures applied for diagnostic ses, etc. A new constitution should determine the grounds and purposes of the deprivation of liberty so that to reduce the number of situations when a citizen may be deprived of liberty. Some measures consisting in deprivation of liberty should be eliminated, e.g. executive measures. The grounds and duration of preliminary" detention should be reduced, with the right to apply that measure vested exclusively in a court. The maximum duration of arrest without the court decision should not exceed 24 hours, and the arrested should be informed immediately about the grounds of arrest. In general, preventive measures should be applied only in order to secure the right course of proceedings. A new constitution should also contain the regulation concerning the damages for illegal deprivation of liberty and should provide for the interdiction to apply physical and psychical torture and other forms of inhuman or humiliating treatment to people deprived of liberty.
Constitutional guaranties of personal freedom.. De lege ferenda considerations